Spotted fever group rickettsiae in black rats, pets, and humans in Zungarococha community, A rural area in the surroundings of Iquitos, Peru - Cusi Ferradas; Guillermo Salvatierra; David Payahuanca; Winnie Contreras; Andrés M. López-Pérez; Therangika A. Hangawatte; Diana León; Bruno M. Ghersi; Ricardo Gamboa; Katia Manzanares Villanueva; Viviana Pinedo-Cancino; Risa Pesapane; et al. (Ticks and Tick-Borne Diseases)
Rickettsiae are a family of ectoparasite-borne bacteria that can produce high morbidity and mortality among humans. There are scarce data on rickettsial ecology in rural areas of the Peruvian Amazon basin, where seroprevalence has not been determined, and the identities of animals acting as reservoirs of these bacteria are not known. We conducted a cross-sectional study in Zungarococha (between 2019 and 2021), a rural community located approximately 20 km away from Iquitos city. Blood samples were collected from humans (175), dogs (123), and cats (12). Blood samples and tissues were collected from black rats (84). Finally, we collected fleas from dogs and cats (222), ticks from dogs (91), and mites from black rats (32). Blood samples from humans, dogs, cats, and black rats were analyzed by indirect immunofluorescence assays (IFA) to detect IgG antibodies against rickettsias. We screened ectoparasites and black rat tissues by real-time-PCR (qPCR). Positive ectoparasites were further assessed by PCR and DNA amplicon sequencing. Non-parametric tests were used to evaluate factors associated with being seropositive among human adults. IgG seroprevalences were 38.3 %, 58.5 %, 16.7 % and 48.1 % among humans, dogs, cats, and rats, respectively. Among humans, only male gender was statistically associated with having IgG antibodies against Rickettsia spp. (p-value=0.049, chi-square test). Different ectoparasites were identified, including Ctenocephalides felis from cats and dogs, Rhipicephalus sanguineus s.l. from dogs, and Laelaps nuttalli from black rats. Rhipicephalus sanguineus s.l. (2/91 ticks) and Ct. felis (53/56 fleas and 55/55 flea pools) were qPCR-positive for Rickettsia spp. Recovered genetic material from 53 Ct. felis was sequenced and all were identified as Rickettsia asembonensis. All tissue samples from black rats were negative by qPCR. Humans, dogs, cats, and black rats are exposed to spotted fever group rickettsiae in rural areas surrounding Iquitos. As reported in urban areas, R. asembonensis is the main Rickettsia species circulating in rural areas surrounding Iquitos and Ct. felis appears to be the main vector.